Structural Vibration Analysis of Historical Drum Tower Structure Caused by Underground Train Running - Zhou, Yefei; Bai, Xiaoxiao; Wang, Shengnian; Zhao, Kai; Su, Hui; Wang, Haiyan (Frontiers in Earth Science, 2022)
The vibration of Metro Operation could have significant impacts on the safety of building structures. In this study, the dynamic response of the Nanjing Drum Tower affected by the Metro Line 4 Operation was investigated by a three-dimensional FEM coupling train-track-tunnel-foundation-soil-watchtower-Drum Tower model performed on a 64 CPU parallel computing cluster platform. The results show that the vertical vibration caused by the subway operation has a more serious impact on the structure of the Drum Tower than that of the horizontal vibration. The vertical vibration decreases from the bottom to the top with a steeper decline trend. The horizontal vibration increases from the bottom of the watchtower to the top of the roof beam overall but is weakened at the roof beam. As the speed of the train increases, the amplitude of horizontal and vertical vibration increases gradually from the bottom of the tower to the roof beam, despite a relatively smaller increase for the horizontal vibration. The double-track operation cases show that the vertical vibration amplitude is much larger than that of the single-track operation, and no significant difference is found in the horizontal direction. The maximum horizontal vibration velocity amplitudes for the watchtower and Drum Tower are 0.131 and 0.060 mm/s respectively.